Experimental Study of the Thermal Diffusivity and Heat Capacity Concerning Some Duplex Stainless Steel - Abdul Abas, Riad Harwill; Taieh, Nabil Kadhim (Al-Khwarizmi Engineering Journal, 2015)
Abstract In the present work, thermal diffusivity and heat capacity measurements have been investigated in temperature range between RT and 1473 K for different duplex stainless steel supplied by Outokumpu Stainless AB, Sweden. The purpose of this study is to get a reliable thermophysical data of these alloys and to study the effect of microstructure on the thermal diffusivity and heat capacity value. Results show the ferrite content in the duplex stainless steel increased with temperature at equilibrium state. On the other hand, ferrite content increased with increasing Cr/Ni ratio and there is no significant effect of ferrite content on the thermal diffusivity value at room temperature. Furthermore, the heat capacity of all samples increases with temperature from room temperature to 473 K, while it decreases with increasing temperature until 1073 K. Then it increases with temperature at higher temperature. Curie temperature and sigma phase formation temperature can be detected by heat capacity-temperature curves. Keywords: Duplex Stainless Steel, Thermal Diffusivity, Thermal conductivity.